Kryzys bankowy w Tajlandii - przebieg kryzysu i sposoby jego opanowywania - Ostalecka, Agnieszka (Banking crisis in Thailand - the course of the crisis and the ways of Its overcoming, 2007)
The article discusses the course of banking crisis and the most important interventional activity taken by the authorities of Thailand which were connected with bringing under control the banking crisis which took place in the years 1997-1999. These actions were proceeding in two directions. The first group of applied remedies consisted in decreasing shrinking liquidity in banking system. However, the second group concentrated on restoring confidence to banking sector. In spite of success in overcoming the crisis, it caused a lot of severe consequences for the Thailand economy and its banking system, as well as for other countries by originating Asian crisis.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1186, s. 88-98